Study of abrasive wear resistance of Fe-based nanostructured hardfacing - Gualco, Agustín (2016)
In the last years several consumables which deposit hard nanostructured iron-based alloys with high resistance to abrasive wear have been developed. The microstructure of the weld metal usually shows variations with the welding procedure, particularly related to the heat input, number of layers and shielding gas type. The purpose of this work was to study the microstructural evolution and wear resistance of a nanostructured iron-based alloy deposited by FCAW process. Four samples with one and two layers were deposited under Ar-20%CO2 shielding and without shielding gas, using a heat input of 3.5 kJ/mm. For each condition chemical composition was determined and microstructure was studied using both optical and electronic microscopy and X ray diffraction. Microhardness and abrasive wear resistance were measured. The microhardness of the deposit was found between 780 and 1020 HV2, depending on the number of layers. There was a variation of the chemical composition between the first and the second layer. The wear test results were discussed in relation to chemical composition, microstructure and microhardness.